Effect of Capacity for Care on cat admission trends at the Guelph Humane Society, 2011–2015. Issue 3 (3rd July 2018) - Janke, Natasha; Berke, Olaf; Klement, Eyal; Flockhart, D.T. Tyler; Coe, Jason; Bateman, Shane
ABSTRACT: In recent years, there has been a growing concern regarding populations of cats who are homeless. Shelters are constantly overwhelmed by the influx of cats without caregivers and are seeking solutions to enhance positive outcomes for them. In 2014, the Guelph Humane Society implemented a population management program to expedite the movement of cats through the shelter by decreasing the average nonhuman animal's length of stay using scheduled intakes to control for overcrowding and by implementing strategies to increase adoption rates. This study investigated the time trends in admission rates of cats to the Guelph Humane Society to assess the effectiveness of a population management program called Capacity for Care using a generalized linear autoregressive moving average model. From January 2011 to December 2015, a total of 3295 live cats were admitted to the Guelph Humane Society. When the analysis was adjusted to account for admissions of kittens, there was a significant reduction in admissions for adult cats ( p  < .01) following the introduction of the population management program. The results also showed a strong seasonal peak in total admissions during the summer months.